Revisiting the Agency Problem and Challenging the Agency Theory through Theoretical Triangulation: A Conceptual Paper - Wijesinghe, C. J.; Wijeyaratne, J. (Faculty of Commerce and Management Studies University of Kelaniya, 2024)
This paper revisits the Agency problem arises due to their unethical practices engaged in market entry strategies, between local agents and principal foreign universities. Further, intends to explore unethical practices and redefine the agency problem more holistically, engaged in the unregulated non-state higher education sector, by revisiting the agency theory through theoretical triangulation. By adopting an inductive approach, researchers justify the choice of methodology as qualitative within interpretive philosophy. Further, employs a multiple case study, filtered from a preliminary qualitative longitudinal study of purposive judgmental sample of 120 agents from 2017-2022, self-administered through unstructured open-ended interviews, observation of their behavior, administrative records, credentials, investigated via online. This paper refines the constructs of agency problem and provides an operational definition in terms of an individual or organization wide intentionality, driven by environmental determinants, internal drives and dispositions of self or organizational actors to commit a conflicting act beyond the intentions of the principal. Thematic analysis of data is engaged through NVivo 14 assuring quality criteria of the research. Managerial contribution of this paper highlights on the necessity of evidence-based policy formulation with international partnerships on mitigating unethical practices in the unregulated non–state higher education sector.
Keywords: Agency problem; Agency theory; Market entry strategies; Theoretical triangulation; Unethical practices.